Urinary Biomarkers and Patient Outcome in Chronic Kidney Disease and Atherosclerotic Heart Disease: The value of IgM-uria and IgG-uria - Tofik, Rafid (Lund University Faculty of Medicine Doctoral Dissertation Series, 2014)
Risk stratification of patients with chronic kidney disease and atherosclerotic heart disease is crucial. Microalbuminuria (MA) is associated with an increased risk of kidney and cardiovascular (CV) death, especially in patients with diabetes. However, MA in many instances is not sensitive for disease outcome; for instance, not all diabetic patients with albuminuria progress to kidney failure, and not all patients with diabetic kidney disease (DKD) have albuminuria. Furthermore, albuminuria is not essentially associated with endothelial dysfunction or glomerular lesions in non-diabetic patients. Urinary excretion of larger proteins, such as IgM and IgG would better reflect glomerular dysfunction and vascular endothelial damage. In this thesis we aimed to evaluate the value of IgG-uria and IgM-uria in predicting kidney and CV outcome in patients with diabetes, glomerulonephritis and atherosclerotic heart disease. In study I, 139 patients with type-1 diabetes, and in study II, 106 patients with type-2 diabetes, were followed at the diabetes outpatient clinic, for an average of 18 and 5 years, respectively. Type-1 & -2 diabetic patients had about a 3-fold increase in CV and renal mortality (HR = 2.7, p = 0.004, and HR = 3.6, p < 0.001, respectively) if they had an increased urine IgM excretion, even when adjusted to the degree of albuminuria. In study III, 178 consecutive patients who presented with acute chest pain to the emergency department of Lund University Hospital were followed for up to 2 years. Patients with acute coronary syndrome had significantly higher baseline IgM-uria than those with non-specific chest pain. Chest pain patients with IgM-uria at time of presentation had a 3-fold higher risk for the occurrence of subsequent major CV event (HR = 3.3, p = 0.001). In study IV, 189 patients with proteinuric primary glomerulonephritis were followed at the nephrology outpatient clinic for an average of 8 years. Patients with an increased urine IgG excretion had an increased risk for end-stage kidney disease (ESKD), even when adjusted for the degree of albuminuria and kidney function (HR = 5.9, p = 0.001). In conclusion, IgM-uria could be a useful biomarker for kidney and cardiovascular risk assessment of patients with diabetes and atherosclerotic heart disease. IgM- uria could imply an extensive atherosclerotic vascular disease. IgG-uria is helpful in identifying patients with glomerulonephritis at increased risk for disease progression to ESKD.
Keywords: Proteinuria; Albuminuria; urine IgM; urine IgG; glomerulonephritis; chronic kidney disease; atherosclerosis; cardiovascular disease; diabetic kidney disease.